Deep enteroscopy in children: techniques, applications, and future directions - Hoskins, Brett J. (Frontiers in Pediatrics, 2025)
Deep enteroscopy, encompassing push enteroscopy (PE) and balloon-assisted enteroscopy (BAE), has revolutionized the diagnosis and treatment of pediatric small bowel disorders. This review examines the evolving role of these techniques in managing conditions such as obscure gastrointestinal bleeding, Crohn's disease, polyposis syndromes, strictures, and small bowel tumors. While PE is effective for both diagnostic and therapeutic interventions in the proximal small bowel, its limited insertion depth has driven the adoption of BAE techniques. These include single-balloon enteroscopy (SBE) and double-balloon enteroscopy (DBE), which provide deeper and more comprehensive access. Both BAE modalities offer greater insertion depth and stability, enabling advanced therapeutic interventions such as polypectomy, stricture dilation, and hemostasis. Pediatric-specific data demonstrate high diagnostic yields for BAE, with comparable outcomes between SBE and DBE. These techniques have proven safe across diverse indications, though younger children may experience slightly higher complication rates due to anatomical considerations. Despite these advancements, challenges persist, including a limited evidence base in pediatrics, barriers to training, and the need for standardized protocols. Additionally, emerging innovations such as artificial intelligence offer opportunities to enhance diagnostic accuracy and procedural efficiency. Comparative analyses of PE, BAE, and capsule endoscopy are necessary to refine procedural selection and optimize outcomes in pediatric patients. Furthermore, structured pediatric training programs and simulation-based learning could address competency gaps, ensuring safe and effective application of these techniques. By addressing current research gaps, embracing technological advancements, and tailoring approaches to pediatric populations, deep enteroscopy can continue to transform the management of small bowel disorders in children.